COOLFACADE: State-of-the-art review and evaluation of solar cooling technologies on their potential for façade integration. (March 2019) - Prieto, Alejandro; Knaack, Ulrich; Auer, Thomas; Klein, Tillmann
Abstract: Increasing cooling demands in the built environment call for innovative technical solutions and systems for application in buildings. Cooling loads represent an important share of the total energy consumption in warm climates, especially in commercial and office buildings. Moreover, mechanical systems will still be needed in most cases to cope with cooling loads, even after considering passive cooling strategies in the design of the building and its façade. Solar cooling technologies present interesting assets, being based on environmentally friendly cooling processes, driven by solar and thus renewable energy. However, their application in the built environment remains greatly limited. This paper assesses several solar cooling technologies in terms of their potential for façade integration; aiming to promote widespread application in buildings throughout the development of integrated architectural façade products. The assessment is based on a state-of-the-art review and discussion of key attributes for façade integration of selected technologies; and a qualitative evaluation of their suitability to respond to main product related barriers for the integration of building services identified in an earlier work by the authors. The cooling principles behind the operation of the assessed technologies have been extensively presented in the literature, so this paper focuses exclusively on key aspects to overcome barriers related to the technical feasibility, physical integration, durability, performance, and aesthetics of future integrated concepts. Results show that the suitability of the assessed technologies varies according to each particular barrier. Hence, no technology currently fits all required aspects. Nonetheless, the use of thermoelectric modules and compact units based on absorption technologies are regarded as the most promising for the development of either integral building components, or modular plug & play systems for façade integration. In any case, this is heavily conditioned to further efforts and explorations in the field to overcome identified challenges and knowledge gaps. Highlights: No assessed technology currently fits all required aspects for façade integration. Technologies' suitability varies according to each façade integration barrier. Current potential was mapped identifying bottlenecks and drafting recommendations. Thermoelectrics and compact units based on absorption technologies are promising. Adsorption/solid desiccant developments should aim to partial façade integration.